PATHOGENIC COMPLEX OF HYBRIDS OF Allium cepa L. IN SOWING CULTURE UNDER DRIP IRRIGATION - S. A. Ferapontova (Овощи России)
The phytopathogenic complex is studied and yield of nine hybrids of bulb onion under growing in annual crops using drip irrigation. The same diseases that afflicted bulb onions in Siberia in the biennial crop of onions are revealed. The highest yield for this technology was shown by F1 hybrid Bonus - 65,5 tones per hectare, average yield - Sherman F1, fopra F1, Solushn F1, Hilton F1.